ANALISIS YURIDIS PERLINDUNGAN HUKUM BAGI PEMENANG LELANG BERDASARKAN PUTUSAN MAHKAMAH AGUNG NO. 251/K/TUN/2016 - VINI VINOLA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting:2. Sutiarnoto3. Faisal Akbar Nasution Auction is the way to sell goods publicly by offering a written form and/or orally which is inclining or declining the highest price. It is usually preceded by an auction announcement. The research used juridical normative and descriptive analytic method. The approach to the research problems is done by analyzing the prevailing legal provisions on legal protection for auction winners. The result of the research showed that a creditor has the authority to execute and sell the collateral which been executed through auction body when debtors default in paying off their debt to creditors. Auction Letter is an authentic deed used by sellers/owners of goods, buyers, and auctioneers to maintain and carry out their right and obligation and to have complete evidence according to Article 1, figure 32 of the Decree of the Minister of Finance No. 27/PMK.06/2016, and the Deed of the Auction Letter can be used by an auction winner to register his land which he has bought through auction.Keywords: Legal Protection, Auction, Auction Winner